Pengaruh Orientasi Pasar, Intellectual Capital, dan Orientasi Pembelajaran Terhadap Inovasi: Studi Kasus pada Industri Hotel di Jawa Timur - Anshori, Mohamad Yusak (Universitas Prasetiya Mulya, 2010)
The purpose of this study was to examine direct and indirect effects of the market orientation, intellectual capital, and learning orientation of the managers on innovation as well was as hotel performance. This study was done at in four and five star hotels in East Java. The respondents were General Manager or Executive Members. The respondents were 180 managers of the 23 four and five star hotels in East Java. It was examined by using SmartPLS 1.01 and reliability was checked using SPSS program Version 14.00. The study showsed that there were significant relations between the ability of the managers in understanding of market orientation, intellectual capital, learning orientation on innovation and hotel performance. The performance of four and five hotels performance in East Java is increased when market orientation, intellectual capital, learning orientation and innovation are increased. Those four variables thoroughly influence hotel performance by 76.4%.